Activated carbons as potentially useful nonnutritive additives to prevent the effect of fumonisin B1 on the sodium bentonite activity against chronic aflatoxicosis. - Monge, Maria del Pilar (2016)
Aflatoxin B1 (AFB1) and fumonisin B1 (FB1) are mycotoxins that often co-occur in feedstuffs. The ingestion of AFB1 causes aflatoxicosis in humans and animals. Sodium bentonite (NaB), a cheap non-nutritive unselective sequestering agent incorporated in animal diets, can effectively prevent aflatoxicosis. Fumonisins are responsible for equine leukoencephalomalacia and porcine pulmonary oedema, and often have subclinical toxic effects in poultries. Fumonisin B1 and aflatoxin B1 are both strongly adsorbed in vitro on sodium bentonite. Co-adsorption studies, carried out with a weight ratio of FB1 to AFB1 that mimics the natural occurrence (200:1), showed that FB1 greatly decreases the in vitro ability of NaB to adsorb AFB1. The ability of two activated carbons to adsorb FB1 was also investigated. Both carbons showed high affinity for FB1. A complex behaviour of the FB1 adsorption isotherms with pH was observed. In vitro results suggest that under natural contamination levels of AFB1 and FB1, a mixture of activated carbon and sodium bentonite might be potentially useful for prevention of sub-acute aflatoxicosis.